Emerging biological observations in prostate cancer. Issue 1 (January 2010) - Shah, Shreya; Small, Eric
Emerging biological observations in prostate cancer provide the opportunity for the development of novel approaches to prevention, detection and treatment. Two observations selected for discussion in this review revolve around the mechanisms of action of signaling through the androgen receptor (AR) and the TMPRSS2:ERG chromosomal rearrangement, a fusion protein seen in nearly 50% of prostate cancers. Despite being called androgen-independent, these prostate cancers continue to depend on AR signaling despite low serum androgen levels. AR reactivation in recurrent tumors is hypothesized to occur through multiple mechanisms: AR amplification, AR mutation, active AR signaling (despite low levels of androgen), AR coactivators, ligand-independent AR activation, enhanced local production of androgens, alternative sources of androgen and upregulation in antiapoptotic genes in prostate cancer cells. A major breakthrough in prostate cancer was the identification of recurrent fusions between the androgen-regulated gene, TMPRSS2 and the v-ets erythroblastosis virus E26 oncogene homolog, ERG . This fusion has been identified as a common molecular event in prostate cancer, seen in approximately 50% of primary prostate cancer. It seems clear that this fusion gene plays an early role in prostate cancer development and/or progression, and ongoing work is being performed to elucidate the association between this fusion transcript and cancer aggressiveness.